Analysis of the relationship between information technology and intellectual capital- Analytical research of the opinions of a sample of decision makers in the Southern General Cement Company - Ali Razzaq Jiyad Al-Abidi (Iraqi Journal for Administrative Sciences, 2024)
This research sought to analyze the relationship between information technology and intellectual capital in the General Company for Southern Cement, so the field of application focused on it and on a problem that can be defined in the following question (Is there a relationship between information technology and intellectual capital?), and more specifically, it attempts to answer the questions The following represents the essence of the research problem: (1) Does adopting information technology and intellectual capital contribute to achieving the organization’s goals? (2) Do individuals in the researched organization have a clear perception of information technology and intellectual capital? (3) Is there a correlation between information technology and intellectual capital? The research also sought to achieve a number of objectives, namely identifying the nature of the variables investigated in the company, as well as identifying relationships. The relationship between the components of information technology and the elements of intellectual capital. In order to achieve the objectives of the research, a hypothetical model was built that determines the nature of the relationship between the independent variable (components of information technology) (computer, software, communication network) and the dependent variable (elements of intellectual capital (human resources, intellectual assets, intellectual property). Choosing the General Company for Southern Cement as a research community, one of the most important companies in the industrial sector in Iraq, as the research sample consisted of (32) questionnaire forms distributed among the decision makers in the company, the management team, which consists of the general manager and his assistants, members of the board of directors, and department managers who are members of the board of directors. A set of statistical methods were also used to analyze the data, based on a five-point Likert scale in designing the questionnaire form, and a correlation coefficient to determine the relationship between the research variables, and the results were obtained using the computer program (SPSS, 10.10). Thus, a set of conclusions were reached The analytical aspect and acceptance of research hypotheses concern the existence of a correlation between information technology and intellectual capital, and based on the conclusions reached by the research, a set of recommendations have been developed that are consistent with the reality of the research.